PENGARUH CURRENT RATIO (CR), RETURN ON ASSET (ROA) DAN STRUKTUR MODAL TERHADAP HARGA SAHAM PADA PT INDOFOOD SUKSES MAKMUR TBK PERIODE 2014-2023 - Mirnawati; Syakhrial (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Current Ratio, Return on Asset, and Capital Structure on stock prices at PT Indofood Sukses Makmur Tbk for the period 2014-2023. The method used is quantitative method. The sample used is data from notes on the statement of financial position, income statement, and stock price information of PT Indofood Sukses Makmur Tbk for the period 2014-2023. The data collection method uses the documentation method through the official IDX website: www.idx.co.id. The results of the study based on the t test Current Ratio partially has a negative effect on stock prices with a significant value of 0.026 <0.05 and a tcount value of -2.732> t table 2.447. Return on Asset partially has no effect on stock prices with a significant value of 0.958> 0.05 and a tcount value of -0.054 < t table 2.447. Capital Structure has no partial influence on stock prices with a significant value of 0.208> 0.05 and a tcount value of -1.371 < t table 2.447. Based on the F test Current Ratio, Return On Asset and Capital Structure there is no simultaneous influence on stock prices, it can be seen the results of Fcount 3.976 < Ftable 4.74 with a significant level of 0.071 > 0.05. Based on the coefficient of determination test, the R Square value is 0.665 or 66.5%, meaning that Current Ratio, Return on Asset and Capital Structure contribute to stock prices by 66.5%, while 33.5% is influenced by other variables.